2008
DOI: 10.1007/s00431-007-0647-0
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted cerebellar development in preterm infants is associated with impaired neurodevelopmental outcome

Abstract: The unfavorable impact of prematurity on the developing cerebellum was recently recognized, but the outcome after impaired cerebellar development as a prematurity-related complication is hitherto not adequately documented. Therefore we compared 31 preterm patients with disrupted cerebellar development to a control group of 31 gender and gestational age matched premature infants with normal cerebellar development. Supratentorial brain injuries during the neonatal period were comparable between the groups. At a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 44 publications
(59 reference statements)
4
80
0
1
Order By: Relevance
“…Even though support for the involvement of the cerebellum in affective and behavioral regulation processes has emerged from psychiatric studies and from studies on children with congenital cerebellar malformations, it is still unclear if these problems correspond to the phenotype of problems resulting from acquired cerebellar lesions during development [34][35][36][37]45]. The results of the questionnaires revealed that the patients experienced just minor emotional distress.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Even though support for the involvement of the cerebellum in affective and behavioral regulation processes has emerged from psychiatric studies and from studies on children with congenital cerebellar malformations, it is still unclear if these problems correspond to the phenotype of problems resulting from acquired cerebellar lesions during development [34][35][36][37]45]. The results of the questionnaires revealed that the patients experienced just minor emotional distress.…”
Section: Discussionmentioning
confidence: 91%
“…Thus far, it is known that children who suffer from congenital vermal aplasia (Joubert-Boltshauser syndrome) have severe cognitive deficits [35]. Other reports have linked an underdevelopment of the cerebellum in preterm babies with potential cognitive problems later in life [36][37][38]. The majority of pediatric studies focusing on cognition after acquired cerebellar lesions have mainly recruited patients suffering from oncological diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Core items of the M-CHAT include joint attention, interest in other children, responding to being called by name and imitating. Extreme prematurity is a major risk factor for cerebellar lesions ( figure 15) and is related to poorer outcome (Messerschmidt et al 2008). Compared to controls, cerebellar injury resulted in 37% positive screen on M-CHAT and between 37-48% incidence of impairments in expressive language, delayed receptive language, cognitive deficits and motor disabilities (Limperopoulos et al 2007).…”
Section: Very Low Birth Weightmentioning
confidence: 99%
“…However, no data are available that describe the developmental expression of SV2 in the chick central nervous system, including the cerebellar cortex, a brain region involved in epileptic disorders (Messerschmidt et al, 2008). We used the calcium-binding protein Calbindin as a marker for Purkinje cells (Celio, 1990), to better follow the development of Purkinje cell processes and localize the SV2 staining.…”
mentioning
confidence: 99%